2015
DOI: 10.1002/2014gl062404
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and mixing state of aged soot particles at a remote marine free troposphere site: Implications for optical properties

Abstract: The radiative properties of soot particles depend on their morphology and mixing state, but their evolution during transport is still elusive. Here we report observations from an electron microscopy analysis of individual particles transported in the free troposphere over long distances to the remote Pico Mountain Observatory in the Azores in the North Atlantic. Approximately 70% of the soot particles were highly compact and of those 26% were thinly coated. Discrete dipole approximation simulations indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
187
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(201 citation statements)
references
References 58 publications
10
187
1
Order By: Relevance
“…Conversely, the BC from the main islands of Japan was relatively fresh (or "uncoated"), thereby maintaining its larger surface area. For example, China et al (2015) clearly showed the morphology of soot particles that are thinly and heavily coated [42], and Moffet et al (2016) reported that all soot particles in urban air were associated with organic carbon, and that soot was frequently at the center of particles as inclusions with thin or thick organic coatings [45]. Apparently this coating would cause the reduction of the surface area of soot particles.…”
Section: Monthly Correlations Between Aerosol Surface Area and Bc Conmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the BC from the main islands of Japan was relatively fresh (or "uncoated"), thereby maintaining its larger surface area. For example, China et al (2015) clearly showed the morphology of soot particles that are thinly and heavily coated [42], and Moffet et al (2016) reported that all soot particles in urban air were associated with organic carbon, and that soot was frequently at the center of particles as inclusions with thin or thick organic coatings [45]. Apparently this coating would cause the reduction of the surface area of soot particles.…”
Section: Monthly Correlations Between Aerosol Surface Area and Bc Conmentioning
confidence: 99%
“…From our results, therefore, we can conclude that the BC from the Asian continent did not have a large surface area but had a high mass concentration, whereas, the mass concentrations of BC transported by easterly wind was low, but that BC had a larger surface area. A possible explanation for this is that some chemical compounds were adsorbed by (or "coated") the surface of the BC during its long-range transport [42][43][44][45], thereby reducing its surface area. Conversely, the BC from the main islands of Japan was relatively fresh (or "uncoated"), thereby maintaining its larger surface area.…”
Section: Monthly Correlations Between Aerosol Surface Area and Bc Conmentioning
confidence: 99%
“…High magnification TEM images demonstrate that typical soot spheres display the onion-like structures with disordered graphitic layers as shown in Figure 1g. They are from incomplete combustion of fossil fuels and other materials [23]. TEM images of primary individual particles: (a,b) mineral particles, (c) spherical organic particle, (d) near-spherical organic particle, (e) aged soot particle and (f) chain-like soot particle; (g) amplified soot spherical.…”
Section: Nature Of Individual Aerosol Particlesmentioning
confidence: 99%
“…High magnification TEM images demonstrate that typical soot spheres display the onion-like structures with disordered graphitic layers as shown in Figure 1g. They are from incomplete combustion of fossil fuels and other materials [23].…”
Section: Nature Of Individual Aerosol Particlesmentioning
confidence: 99%
“…Recent studies show that internal mixing of BC with other aerosol materials in the atmosphere can alter its aggregate shape (Zhang et al, 2008;Xue et al, 2009;Cross et al, 2010;China et al, 2013), absorption of solar radiation (Bueno et al, 2011;Cappa et al, 2012b), and radiative forcing (Adachi et al, 2010;Kahnert et al, 2012). China et al (2014), furthermore, characterized the predominant mixing and morphology types observed with the electron microscopes from samples collected in different locations and for different sources (i.e., biomass burning aerosol and vehicle exhaust) by classifying BC into four main classes (bare BC, inclusions, thinly coated and embedded BC); similar classes where identified by Scarnato et al (2013) for laboratory-generated mixtures of BC and sodium chloride (an aerosol mixture resembling dirty marine aerosol).…”
Section: B V Scarnato Et Al: Optical Properties Internally Mixed Mmentioning
confidence: 99%